Comparative physical, chemical and biological assessment of simple and titanium-doped ovine dentine-derived hydroxyapatite coatings fabricated by pulsed laser deposition - OKTAR, FAİK NÜZHET; GÜNDÜZ, OĞUZHAN (ELSEVIER SCIENCE BV, 2017)
We report on the synthesis by Pulsed Laser Deposition of simple and Ti doped hydroxyapatite thin films of biological (ovine dentine) origin. Detailed physical, chemical, mechanical and biological investigations were performed. Morphological examination of films showed a surface composed of spheroidal particulates, of micronic size. Compositional analyses pointed to the presence of typical natural doping elements of bone, along with a slight non-stoichiometry of the deposited films. Structural investigations proved the monophasic hydroxyapatite nature of both simple and Ti doped films. Ti doping of biological hydroxyapatite induced an overall downgrade of the films crystallinity together with an increase of the films roughness. It is to be emphasized that bonding strength values measured at film. Ti substrate interface were superior to the minimum value imposed by International Standards regulating the load-bearing implant coatings. In vitro tests on Ti doped structures, compared to simple ones, revealed excellent biocompatibility in human mesenchymal stem cell cultures, a higher proliferation rate and a good cytocompatibility. The obtained results aim to elucidate the overall positive role of Ti doping on the hydroxyapatite films performance, and demonstrate the possibility to use this novel type of coatings as feasible materials for future implantology applications. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Ti-doped hydroxyapatite; Sustainable resources; Ovine dentine; Implant coatings; Pulsed laser deposition; CALCIUM HYDROXYAPATITE; MICROSTRUCTURAL PROPERTIES; FILMS; TI; PHOSPHATE; ANTIBACTERIAL; SUBSTRATE; BONE